Storytelling as an Effective Educational Tool in Primary Education in Rural Areas of Bangladesh: Teachers’ Perspective (Teacher’s World: Journal of Education and Research, 2023)
This paper discusses the effectiveness of storytelling as a strategy to improve the teaching-learning process for primary school students in Bangladesh's rural areas. The goal of this research is to examine the teachers’ perceptions of the use of storytelling as an educational technique, the degree to which storytelling is employed in educating students, and the impact of storytelling on the teaching-learning process. The qualitative technique is used to acquire information from the respondents in this study. A group of primary school teachers from government primary schools in Ukhiya is interviewed by the researcher s. A number of interview questions were used in order to get information on the perception of the teachers on storytelling and the importance of storytelling from their perspective. The results of the interview session are used to determine how storytelling affects the teaching process in the eyes of the teachers. The finding section of this study includes the major findings of this study. The results indicate that most of the primary teachers in remote areas of Bangladesh prefer to use storytelling as an alternative to textbook content. Moreover, the teachers incorporate storytelling to enhance the learner’s language skills and motivation. It is suggested that the teachers should use a variety of stories to increase the students’ creative and linguistic skills. It is also suggested that the teachers are positive about getting training on storytelling in order to improve their speech, accent, and storytelling delivery.Teacher’s World: Journal of Education and Research, Vol. 48(2), Dec 2022, p.130-141